Organising co-existence in cyberspace: Content regulation and privacy compared - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
The Internet globalizes the world. National regulatory autonomy shrinks. Transferring data from one country to another is almost costless. Foreign content is just a click away. Why is it that states have been able to re-install co-existence in some policy areas, and not in others? In data protection, the safe-harbour compromise between the US and the EU found a way out. In the area of content regulation, transnational conflict is no less pronounced. The Europeans are preoccupied with Nazi publications, that are constitutionally protected in the US. The US public dislikes portrayals of nudity, that most Europeans find inoffensive. Yet no attempts at organizing co-existence are within sight. This paper develops a rational choice model to explain the difference. States are modelled as actors. The good is the degree of protection accorded to a value. Nations evaluate such protection differently. Moreover, rational nations are aware of the opportunity cost involved in any activity to protect local values. To a degree, the inability of organizing co-existence stems from a difference in preferences. If so, there is no room for a win-win solution. But typically, one nation does not positively want some content to be accessible that the other nation dislikes fervently. Usually, the first nation is just indifferent, or the opportunity cost seems too high. The more important difference between data protection and content regulation thus turns out to be strategic. Organizing co-existence in both areas presupposes overcoming a strategic conflict. But in data protection, this typically is a one-to-one conflict, while in content regulation the typical conflict is of a one-to-many nature. In public goods terminology, co-existence is a weaker-link good with a very high threshold. This difference might make it advisable for countries with a strong preference for protection to shift from mitigation to adaptation. Practically speaking, they would push, perhaps even subsidize, the development of powerful filtering technologies. And they would strengthen their social norms ostracizing access to outrageous content.
Keywords: D72; D74; D78; H41; H73; H77; K33; L96; 330; Internet regulation; cyberlaw; data protection; content regulation; Nazi speech; pornography; public goods; international conflict